Should we take sides?: Girard, Mouffe, et al on graceful divisiveness - Christopher Adam Haw (Studia z Teorii Wychowania)
This paper interprets the rhetoric and social phenomena of “taking sides” and “scapegoating” amidst radical societal division. Exploring the social mechanics of unity and division, I visit the work of René Girard and Chantal Mouffe, who offer a lucid ambivalence regarding the dilemma that neutrality is a practical impossibility. And in turning to implications of their shared paradox—that to be genuinely “peaceful” may require graceful divisiveness—I consider cases and theory on nonviolently fomenting conflict. In contrast with certain liberal social theories of transcending division, this paper treats the desire for politics beyond hegemony—or politics without a scapegoat—as something of an eschatological ideal, toward which Girard, Mouffe, and others offer a tension-filled, crypto-Augustinian, agonistic pluralism.